On time dependent orthogonal polynomials on the unit circle - Ben-Artzi, A.; Gohberg, I. (Український математичний журнал, 1994)
Two index formulas for operators defined by infinite band matrices are proved. These results may be interpreted as a generalization of the classical theorem of M. G. Krein for orthogonal polynomials. The proofs are based on dichotomy and nonstationary inertia theory. Доведено дві формули індексу для операторів, визначених матрицями нескінченного порядку. Ці результати можна інтерпретувати як узагальнення класичної теореми М.Г. Крейна про ортогональні поліноми. Доведення базується на дихотомії та нестаціонарній теорії інерції.